Long non-coding RNA NEAT1 inhibits high glucose-induced EMT and renal fibrogenesis in Human Embryonic Kidney 293 cells via regulating miR-204/SOX4 axis: Long non-coding RNA NEAT1 inhibits DN progression - Ahmad Wadaan, Mohammad; Ahmad, Mohammad; Hussein Hamzah, Israa (Cellular and Molecular Biology, 2023)
Diabetic nephropathy (DN) is a severe complication of diabetes that increases mortality worldwide. Long non-coding RNAs (lncRNAs) have been investigated in DN, but the precise molecular mechanism is unclear. The research aimed to study the role of lncRNA NEAT1 in DN using an in vitro model, with the goal of uncovering its potential function and molecular mechanism in the development of DN. High glucose was applied to HEK 293 cells in order to create the DN model. The expression levels of NEAT1, miR-204, and SOX4 were assessed using RT-qPCR, along with the mRNA expression of EMT-related biomarkers and fibrosis markers such as α-SMA, E-cadherin, Vimentin, Fibronectin, and Col IV in HEK 293 cells. The interaction between NEAT1, miR-204, and SOX4 was predicted using Starbase 2.0 and confirmed through dual luciferase reporter assay. In HEK 293 cells treated with high glucose, NEAT1, and SOX4 expression were down-regulated, while miR-204 expression increased in a concentration-dependent manner. NEAT1 activation in HEK 293 cells prevented high glucose-induced fibrogenesis and EMT. NEAT1 directly targeted miR-204, and its inhibitory effects on EMT and fibrogenesis were restored by miR-204 overexpression. NEAT1 also regulated high glucose-induced EMT and fibrogenesis through its influence on miR-204 and SOX4. In conclusion, the miR-204/SOX4 axis is a prospective therapeutic target for the treatment of DN since lncRNA NEAT1 inhibited high glucose-induced EMT and fibrogenesis by controlling it in DN.